Construction of a nickel-rich LiNi0.83Co0.11Mn0.06O2 cathode with high stability and excellent cycle performance through interface engineering. (6th January 2023) - Zhang, Shan; Zhou, Xiaolin; Li, Sihan; Feng, Ze; Fan, Xin; Sun, Dan; Wang, Haiyan; Tang, Yougen
Abstract : Nickel-rich cathodes of LiNi0.83 Co0.11 Mn0.06 O2 (NCM83) are receiving increased attention due to its high specific capacity and low cost. Abstract : Nickel-rich cathodes of LiNi0.83 Co0.11 Mn0.06 O2 (NCM83) are receiving increased attention due to its high specific capacity and low cost. Nevertheless, the excess residual lithium, unsatisfactory cycle performance and poor thermal stability limit its further commercial application. Herein, we proposed an effective strategy to improve the electrochemical properties of NCM83 by Li4 Mn5 O12 coating. The uniform lithium-rich coatings of Li4 Mn5 O12 are derived from the reaction between manganese(ii ) acetylacetonate and the alkaline lithium impurities, which can efficiently reduce the residual lithium, improve the interfacial Li-ion diffusion kinetics, and suppress the interfacial side reaction. As a result, the coated cathodes show excellent cycle stability and thermal stability. Typically, the Li4 Mn5 O12 (LMO) coated sample of NCM83@LMO-2 displays a higher discharge capacity of 169.8 mA h g −1 at 1 C with 93.2% capacity retention after 100 cycles, which is much higher than the pristine NCM83 (139.9 mA h g −1 with 76.5% capacity retention). This work provides an in-depth understanding on how to improve the interfacial properties of Ni-rich materials and enhance the electrochemical performances, thereby facilitating the commercial application of high-energy-density lithium-ion batteries.